Pedagogy of discomfort to prevent and intervene against bias-based bullying - Thomassen, Wenche Elisabeth; Moi, Anna L.; Langvik, Kjersti Merete; Skeie, Geir; Fandrem, Hildegunn (Frontiers in Education, 2024)
In this article we will present bias-based bullying episodes shared by Norwegian teachers and preservice teachers when talking about the concept of 'discomfort'. We also investigate how 'discomfort' and 'pedagogy of discomfort' as a tool is reflected in teachers and preservice teachers' prevention and intervention of bias based bullying episodes.Semi-structured interviews were conducted among seven preservice teachers in their last year of teacher education, and seven teachers, with 7 -24 years of experience, working in Norwegian schools.Our main findings indicate that the pedagogy of discomfort might be a useful tool to prevent and intervene against bias-based bullying by using the feeling of discomfort that bias-based bullying creates in a constructive way. However, while the preservice teachers are inspired by theories of discomfort and social justice education and are motivated to try those theories out in practice, the teachers were not so familiar with these theories and tended to manage discomfort by avoiding it. By getting more familiar with the pedagogy of discomfort, teachers may improve classroom atmosphere and make it easier to explore difficult topics in a way that create room for differences and inclusion and strengthen students and teachers` ability to critical thinking and thus lower the risk of bias based bullying.